Unravelling Affective Mathematical Disposition: Its Role in Strengthening Numeracy Among Pre-Service Mathematics Teachers - Soesanto, Robert Harry; Dirgantoro, Kurnia Putri Sepdikasari (Jurnal Pendidikan MIPA, 2025)
This study investigates the relationship between affective mathematical disposition (MD) and numeracy among pre-service mathematics teachers in Indonesia. The research examines explicitly how different dimensions of MD influence students' numeracy skills. A total of 237 participants took part in a semester-long numeracy enrichment program, followed by a numeracy assessment and an MD questionnaire based on Beyers' seven affective dimensions. Using multiple linear regression analysis, the findings indicate that MD significantly affects numeracy (p = 0.018), with an adjusted R-squared value of 0.571, indicating that 57.1% of the variance in numeracy scores can be explained by MD. Notably, the dimensions "Nature in Mathematics" (β = 0.584, p = 0.033) and "Mathematics Self-Concept" (β = 0.612, p = 0.016) exhibit significant positive influences on numeracy. Highlighting the role of conceptual understanding and self-perception in mathematical learning. These results align with the program’s design, which emphasized conceptual understanding and reflective self-assessment elements directly tied to both dimensions. However, other dimensions, including "Usefulness," "Worthwhileness," "Sensibleness," "Attitude," and "Math Anxiety," did not show significant effects. This may be due to participants' shared perceptions as mathematics teacher candidates, resulting in low variability on those dimensions, or due to possible mediation effects (e.g., motivation) that were not examined in this study. The findings suggest that interventions aiming to strengthen numeracy should focus on enhancing students’ understanding of mathematical structures and fostering a strong self-concept as mathematics learners. This study contributes to mathematics education by highlighting the specific affective dimensions that most directly relate to numeracy, providing a nuanced perspective for teacher educators seeking to balance cognitive and affective development in their curriculum.   Keywords: mathematical disposition, affective domain, numeracy, pre-service mathematics teachers, mathematics education.